Layanan Dasar Bimbingan Dan Konseling untuk Peningkatan Survival And Safety Skills Siswa - Putri, Vany Dwi; Nakhma’ussolikhah, Nakhma’ussolikhah (Universitas Islam Bunga Bangsa Cirebon, 2020)
Survival and Safety Skills is a skill that must be acquired by every individual. One way to improve survival and safety skills is to provide a guidance curriculum of guidance and counseling. The goal of the research is to obtain the depiction of the students’ survival and safety skills which will be the basis to develop the guidance curriculum. A quantitative approach with descriptive methods was used in the research. The instrument in the study was questionnaire in form of scale that was developed based on indicators of junior high school students’ survival and safety skills from Comprehensive School Counseling Program Guide 2009. The population of the study was all eighth grade students of SMP Miftahul Iman in Academic Year 2018/2019. The results showed that the level of the students’ survival and safety skills was in the adequate category. The developed basic guidance was developed based on the the processed data. Based on the study, it is recommended for the school to work with other parties, including students’ parents, to improve the students’ survival and safety skills. Counselors can collaborate with the school, homeroom teachers, and other teachers in order to gather information related to the students’survival and safety skills. Keywords: Survival and Safety Skills; Students of SMP; Guidance Curriculum Of Guidance And Counseling. Abstrak Survival and Safety Skills adalah suatu keterampilan yang harus dimiliki oleh setiap individu. Salah satu cara untuk meningkatkan survival and safety skills adalah dengan memberikan layanan dasar bimbingan dan konseling. Tujuan penelian adalah memperoleh survival and safety skills siswa yang dijadikan landasan dalam pembuatan layanan dasar bimbingan dan konseling. Penelitian menggunakan pendekatan kuantitatif dengan metode deskriptif. Alat pengukuran data adalah kuiseoner berbentuk skala yang dikembangkan berdasarkan indikator survival and safety skills untuk SMP dari Comprehensive School Counseling Program Guide 2009. Populasi penelitian adalah seluruh siswa kelas VIII SMP Miftahul Iman Tahun Ajaran 2018/2019. Hasil penelitian menunjukkan tingkat survival and safety skills yang dimiliki siswa berada pada kategori cukup. Layanan dasar yang dikembangkan disesuaikan dengan hasil pengolahan data yang telah dilakukan. Secara umum, survival and safety skills siswa berada pada kategori cukup. Rekomendasi penelitian ditujukan bagi pihak sekolah agar dapat melakukan kerjasama yang baik dengan pihak luar maupun orang tua untuk meningkatkan survival and safety skills siswa. Guru BK dapat melakukan bekerjasama dengan pihak sekolah, wali kelas dan guru mata pelajaran untuk mengumpulan informasi terkait survival and safety skills siswa. Kata Kunci: Survival and Safety Skills; Siswa SMP; Layanan Dasar Bimbingan dan Konseling.